When it is no longer a bit of banter: Coaches' perspectives of bullying in professional soccer. Issue 6 (2nd November 2022) - Newman, James A.; Eccles, Stephen; Rumbold, James L.; Rhind, Daniel J. A.
ABSTRACT: Studies exploring bullying in sport psychology remain relatively limited despite various media reports of the abusive practice of some professional soccer coaches. This research explores coaches' views of bullying in professional soccer academies and how it is framed in relation to banter. Five professional soccer coaches were interviewed using a semi-structured interview guide. The methodology and analysis were guided by interpretative phenomenological analysis. Coaches highlighted key components which identify bullying in professional soccer environments, such as intent to harm; frequency of behaviour; and an imbalance of power. Coaches also highlighted different individual and contextual factors which separated bullying from banter. These included individual differences; unintentional behaviour; immaturity; and the masculinity of the soccer culture. These findings provide an important extension to the bullying literature in sport by highlighting coaches' own perspectives on this concept within the professional soccer context. The findings also illustrate the subtle nuances through which coaches separate bullying from banter. As such, important applied implications are discussed for the development of coach education programmes to raise greater awareness around these concepts as well as the potential consequences of bullying and banter on player welfare in professional soccer.